Impact of the EU funds on the diversification of economic activity (of farms) and their role in multi-functional development of rural areas - Biczkowski, Mirosław; Biczkowska, Marta (PAN IGiPZ, 2016)
The focus of the article is on two issues. One of them is related to the process of multi-functional development of rural areas; the other one concerns the impact the European Union funds have on diversification of economic activity in rural areas. The study attempts to assess this impact with regard to diversification of sources of income gained by rural population and, consequently, with regard to multi-functionality of rural areas. The analysis was based on the number of applications processed and funds acquired within the measures under Axis 3 of the Rural Development Programme 2007–2013 which have provided the most substantial support for multi-functional development of rural areas, i.e. ‘Diversification into non-agricultural activities’ and ‘Creation and development of micro-enterprises’.
24 cm
Keywords: multi-functional development; non-agricultural activity; RDP; EU funds; rural areas; diversification of agricultural activity